Which expressions are equivalent to -56z+28−56z+28minus, 56, z, plus, 28?
Choose 2 answers:
Choose 2 answers:

(Choice A)
A
\dfrac{1}{2}\cdot(-28z+14)
2
1

⋅(−28z+14)start fraction, 1, divided by, 2, end fraction, dot, left parenthesis, minus, 28, z, plus, 14, right parenthesis

(Choice B)
B
(-1.4z+0.7)\times40(−1.4z+0.7)×40left parenthesis, minus, 1, point, 4, z, plus, 0, point, 7, right parenthesis, times, 40

(Choice C)
C
(14-7z)\cdot(-4)(14−7z)⋅(−4)left parenthesis, 14, minus, 7, z, right parenthesis, dot, left parenthesis, minus, 4, right parenthesis

(Choice D)
D
(8z-4)(-7)(8z−4)(−7)left parenthesis, 8, z, minus, 4, right parenthesis, left parenthesis, minus, 7, right parenthesis

(Choice E)
E
-2(-28z-14)−2(−28z−14)

Respuesta :

Answer:

B) [tex](-1.4z+0.7)\times 40[/tex]

D) [tex](8z-4)(-7)[/tex]

Step-by-step explanation:

Given expression:

[tex]-56z+28[/tex]

To find the equivalent expression.

We will evaluate each expression in the given choices to check the equivalence.

A) [tex]\frac{1}{2}(-28x+14)[/tex]

Using distribution.

⇒ [tex]\frac{-28z}{2}+\frac{14}{2}[/tex]

⇒ [tex]-14z+7[/tex]

B) [tex](-1.4z+0.7)\times 40[/tex]

Using distribution.

⇒ [tex](-1.4z\times 40)+(0.7\times 40)[/tex]

⇒ [tex]-56z+28[/tex]

C) [tex](14-7z).(-4)[/tex]

Using distribution.

⇒ [tex](14.(-4))+(-7z.(-4))[/tex]

⇒ [tex]-56+28z[/tex]

D) [tex](8z-4)(-7)[/tex]

Using distribution.

⇒ [tex](8z(-7))+(-4(-7))[/tex]

⇒ [tex]-56z+28[/tex]

E) [tex]-2(-28z-14)[/tex]

Using distribution.

⇒ [tex](-2(-28z))+(-2(-14))[/tex]

⇒ [tex]56z+28[/tex]

From the choices evaluated, we find that the expressions in choices B and D are equivalent

Answer:

A and C

Step-by-step explanation:

khan